Komparasi Kompetensi Pedagogik dan Kompetensi Profesional Guru yang Sudah Bersertifikasi dan Guru yang Belum Bersertifikasi pada Sekolah Dasar Negeri - Dwi Wachjuni; Maria Ulpah; Benny Agus Pribadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
This study's purpose is to know the pedagogical and professional competence of teachers who have education certificates and those who do not yet have education certificates, and to understand that the pedagogical and professional competence of certified teachers is higher than uncertified teachers at the public elementary school in Ajibarang District, Banyumas. This quantitative research was done at a state elementary school in Ajibarang District, Banyumas. The research sample was 92 teachers, divided by 46 who have certificates and 46 who have not had certificates. Data used were primary data which collecting by questionnaire distribution. Data analyzed by t-test independent sample. This research concludes that certified teachers have a high pedagogical competence, and the pedagogical competence of uncertified teachers is lower. The professional competence of certified teachers is high, and the professional competence of uncertified teachers is lower. Paedagogic and professional competence of certified teachers are better than uncertified ones at the public elementary school in Ajibarang District Banyumas.